Temperature Increase and Specific Absorption Rate Distribution in Human Breast from Cell Phone Radiation - ÇALLIALP, FULYA (AMER SCIENTIFIC PUBLISHERS, 2018)
This study describes the cell phone radiation effect on the healthy and unhealthy female breast tissue to establish safety criteria and to detect the cancerous tissue. A computational modeling is performed at 900 MHz and 1800 MHz with a sphere shaped breast and cancerous tissue in different configurations. Thermal investigation is performed through the heat transfer equation to determine temperature and specific absorption rate elevation in the female breast tissue. First, healthy breast tissue is excited with an antenna of which distances to the breast is varying. Next, the distribution of temperature and specific absorption rate are estimated on the different radius of cancerous breast tissue which is located at the center and at the bottom of the breast, respectively. The simulated temperature and the specific absorption rate values imply that the values are ascending with the size of the tumor whereas descending as the source is positioned further.
Keywords: Specific Absorption Rate; Breast Tumor Tissue; Cell Phone Radiation; THERMOGRAPHY